1993
DOI: 10.3109/15513819309048204
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pulmonary Bombesin Immunoreactive Cells in Wilson-Mikity Syndrome (Pulmonary Dysmaturity) and Bronchopulmonary Dysplasia

Abstract: Wilson-Mikity syndrome (WMS) is a disorder of uncertain origin. It is sometimes considered a variant of bronchopulmonary dysplasia (BPD), but it lacks the characteristic microscopic stigmata of destruction and fibrosis caused by the barotrauma and oxygen toxicity of ventilator support. Conventional clinical and autopsy studies of WMS have failed to identify the underlying pathophysiology. This study evaluated bombesin-containing pulmonary neuroendocrine (PNE) cells in eight WMS cases, seven cases of BPD, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Previous studies of the same material have shown that PNEC and NEBs are numerous in infants with advanced BPD (Johnson et al, 1988;Stahlman et al, 1985Stahlman et al, ,1987Stahlman and Gray, 1984). PNEC hyperplasia has been demonstrated in BPD in other studies as well (Gillan and Cutz, 1993;Johnson et al, 1982Johnson et al, ,1985. The increased numbers of NEBs in advanced BPD may reflect a response to chronic local hyp-oxia and/or increased production of growth factors such as bombesin.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies of the same material have shown that PNEC and NEBs are numerous in infants with advanced BPD (Johnson et al, 1988;Stahlman et al, 1985Stahlman et al, ,1987Stahlman and Gray, 1984). PNEC hyperplasia has been demonstrated in BPD in other studies as well (Gillan and Cutz, 1993;Johnson et al, 1982Johnson et al, ,1985. The increased numbers of NEBs in advanced BPD may reflect a response to chronic local hyp-oxia and/or increased production of growth factors such as bombesin.…”
Section: Discussionmentioning
confidence: 78%
“…Exclusion of other forms of chronic lung disease is also an important consideration, as airway neuroendocrine cell hyperplasia has been described as a secondary fi nding in a wide variety of pediatric lung disorders. [72][73][74][75][76][77][78] Some cases have mild airway-associated lymphoid hyperplasia, but signifi cant fi brosis is absent. The etiology of NEHI remains unknown and it has been suggested that this may be a developmental or genetic disorder due to familial descriptions of NEHI, or may also be a secondary reaction to prior airway injury, for example a postinfectious process or post-aspiration process.…”
Section: Neuroendocrine Cell Hyperplasia Of Infancymentioning
confidence: 98%
“…Most cases are idiopathic ("diffuse idiopathic pulmonary NE cell hyperplasia," associated with obliterative bronchiolar fibrosis in the absence of known causes of interstitial or airway fibrosis or inflammation) [28], while others may be incidentally found in chronic bronchial inflammation [42], Langerhans cell hystiocytosis [2] or bronchopulmonary dysplasia [16].…”
Section: Ne Cells In Normal Lung and In Non-neoplastic Conditionsmentioning
confidence: 99%